Variación en la concentración de alcaloides fúngicos en Festuca rubra del Norte y sur de Europa - Vázquez de Aldana, Beatriz R.; Helander, Marjo; Saikkonen, Kari; Álvarez Pascua, Amador; Zabalgogeazcoa, Iñigo (Sociedad Española para el Estudio de los Pastos, 2016)
6 páginas y 2 tablas.-- Comunicación presentada a la 55ª Reunión Científica de la Sociedad Española para el Estudio de los Pastos (SEEP). Innovación Sostenible En Pastos: Hacia una Agricultura de Respuesta al Cambio Climático. En Lugo-A Coruña (España). 26 a 29 abril del 2016. [EN] Several pasture grasses are commonly infected by Epichloë fungal endophytes. Festuca rubra plants infected by Epichloë festucae may have two types of alkaloids, one toxic to livestock (ergovaline) and other toxic to insects (peramine). In this study, the effect of plant origin and environmental growth conditions on the concentration of alkaloids in plants of F. rubra from south (Spain) and northern Europe (Faroe islands and Finland) pastures was studied in an experimental field trial conducted simultaneously in three experimental plots located in Spain (Salamanca) and Finland (Ruissalo and Kevo). The peramine alkaloid was detected in 53% of the plants from Spain, but was not detected in any plot from northern Europe (Faroe Islands or Finland) was not detected in any plot. Ergovaline was detected in plants from the three sites and the three experimental plots. The highest ergovaline concentration was found in plants from Finland. Comparing experimental plots, the highest ergovaline content was found in both plots from Finland which were significantly higher than that of the Spanish plot. [ES] Los hongos endófitos del género Epichloë infectan de forma asintomática varias especies de gramíneas. Las plantas de Festuca rubra infectadas por Epichloë festucae pueden contener dos tipos de alcaloides, uno tóxico para el ganado (ergovalina) y otro tóxico para insectos (peramina). En este trabajo se estudia el efecto de la procedencia de la planta y de las condiciones de crecimiento (parcela) en el contenido de alcaloides en plantas de F. rubra procedentes de pastos del sur (España) y del norte de Europa (Islas Faroe y Finlandia), en un ensayo experimental de campo llevado a cabo de forma simultánea en tres parcelas experimentales ...